INTEGRATING BLUE ECONOMY AND ISLAMIC PRINCIPLES FOR SUSTAINABLE ECONOMIC AND ENVIRONMENTAL SYNERGY IN THE KARIMUNJAWA ISLANDS - Johan Afandi; Makrufah Hidayah Islamiah (Universitas Sains Al Qur'an, 2026)
This study aims to describe the synergy between the economy and the environment in the Karimunjawa Islands through the implementation of Blue Economy principles based on Islamic values. This research employs a qualitative method with a field research approach. The research subjects consist of five individuals, including related government institutions such as BBPBAP Jepara; the Secretary of HPI Karimunjawa; Karimunjawa residents, lodging owners, fishermen who are also tour boat owners, as well as other stakeholders involved in the management of marine resources. Data were collected through observation, interviews, and documentation using data analysis techniques including data reduction, data display, and conclusion drawing. The results show that the synergy between economic and ecological aspects in Karimunjawa is realized through sustainable practices, such as the use of environmentally friendly fishing gear, aquaculture activities that meet the standards of Good Aquaculture Practices (CBIB), and the development of conservation-based tourism. This is supported by coral reef monitoring data over the past five years, which indicate that the percentage of coral reef cover in the Karimunjawa National Park area falls into the “good” category (average 64.70%), representing an increase compared to the 2019 coverage of 53.80%. Increases occurred in all zones except the marine tourism utilization zone. Public awareness of marine conservation has also increased, along with the understanding that the sea is a source of life and a trust (amanah) from Allah SWT. Islamic principles such as tauhid (unity of God), khalifah (stewardship), maslahah (public benefit), mizan (balance), and anti-israf (prohibition of excess) serve as the foundation for marine economic activities that balance community welfare and ecosystem preservation. Religious traditions such as Sedekah Laut (Lomban) and Barikan Kubro further strengthen the community’s sense of gratitude and ecological responsibility. Thus, the implementation of a Sustainable Blue Economy based on Islamic values in Karimunjawa reflects a model of coastal development that is just, sustainable, and aligned with the principle of environmental balance (hifz al-bi’ah).